Menslike behoeftes as sistematies-teologiese kernbegrip - Pauw, C. J. (Verbum et ecclesia, 2006)
Human needs is not part of the traditional themes of systematic theology or even of theological anthropology. This article argues that human needs is a core concept in systematic theology even though it has not been an explicit theme of systematic theology. The concept of human needs is essentially related to the content of systematic theology. Any articulation of the doctrine of creation, covenant or salvation is underpinned by a view of what human needs are. This article shows that the question of human needs is normally related to systematic theology by referring to the task of systematic theology and the different modes of discourse found in which systematic theology gives expression to this task. This article also suggest a method by which an implicit concept of human needs may be discovered and engaged critically. This is demonstrated by analysis of two designs of theological anthropology: Karl Barth’ s second part of the third volume of his Church Dogmatics and the fundamental-theological anthropology of Wolfhart Pannenberg.